Lehrerprofessionalisierung und Fortbildungsaktivitäten im Kontext von Schulentwicklung mit neuen Technologien - Gerick, Julia; Eickelmann, Birgit (Journal für Schulentwicklung)

Preparing teachers for schooling in the digital age: A meta-perspective on existing strategies and future challenges - Erstad, Ola; Eickelmann, Birgit; Eichhorn, Koos (Education and Information Technologies)

Schulische Prädiktoren für die Nutzung neuer Technologien im Mathematikunterricht der Primarstufe und ihre Zusammenhänge mit Schülerkompetenzen - Eickelmann, Birgit; Gerick, Julia; Bos, Wilfried (IGLU & TIMSS. 10 Jahre international vergleichende Schulleistungsforschung in der Grundschule. Vertiefende Analysen zu IGLU und TIMSS 2001 bis 2011)

Wie geht es weiter? Zentrale Befunde der Studie ICILS 2013 und mögliche Handlungs- und Entwicklungsperspektiven für Einzelschulen - Eickelmann, Birgit; Bos, Wilfried; Gerick, Julia (SchulVerwaltung NRW)

Implementierung eines hybriden Verschlüsselungsverfahrens nach Cramer und Shoup - Kalde, Benedikt

Total digital? - Wie Jugendliche Kompetenzen im Umgang mit neuen Technologien erwerben. Dokumentation der Analysen des Vertiefungsmoduls zu ICILS 2013 - Eickelmann, Birgit; Bos, Wilfried; Vennemann, Mario

Tackling Educational Challenges in a Digitally Networked World - Lai, Kwok-Wing; Davis, Niki; Eickelmann, Birgit; Erstad, Ola; Fisser, Petra; Gibson, David C.; Khaddage, Ferial; Knezek, Gerald; Webb, Mary (KEYCIT 2014. Key Competencies in Informatics and ICT)

Singulärwertzerlegung für μ-ähnliche Bregman-Divergenzen - Strotmann, Daniela

HybridTE: Traffic Engineering for Very Low-Cost Software-Defined Data-Center Networks - Wette, Philip; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
The size of modern data centers is constantly increasing. As it is not economic to interconnect all machines in the data center using a full-bisection-bandwidth network, techniques have to be developed to increase the efficiency of data-center networks. The Software-Defined Network paradigm opened the door for centralized traffic engineering (TE) in such environments. Up to now, there were already a number of TE proposals for SDN-controlled data centers that all work very well. However, these techniques either use a high amount of flow table entries or a high flow installation rate that overwhelms available switching hardware, or they require custom or very expensive end-of-line equipment to be usable in practice. We present HybridTE, a TE technique that uses (uncertain) information about large flows. Using this extra information, our technique has very low hardware requirements while maintaining better performance than existing TE techniques. This enables us to build very low-cost, high performance data-center networks.

IT-Unterstützung in Emergency Management & Response - Erfurth, Christian; Pottebaum, Jens (45. Jahrestagung der Gesellschaft für Informatik, Informatik 2015, Informatik, Energie und Umwelt, 28. September - 2. Oktober 2015 in Cottbus, Deutschland)
Keywords: Ver{\

Towards Establishing Monotonic Searchability in Self-Stabilizing Data Structures - Scheideler, Christian; Setzer, Alexander; Strothmann, Thim Frederik (Proceedings of the 19th International Conference on Principles of Distributed Systems (OPODIS))
Distributed applications are commonly based on overlay networks interconnecting their sites so that they can exchange information. For these overlay networks to preserve their functionality, they should be able to recover from various problems like membership changes or faults. Various self-stabilizing overlay networks have already been proposed in recent years, which have the advantage of being able to recover from any illegal state, but none of these networks can give any guarantees on its functionality while the recovery process is going on. We initiate research on overlay networks that are not only self-stabilizing but that also ensure that searchability is maintained while the recovery process is going on, as long as there are no corrupted messages in the system. More precisely, once a search message from node u to another node v is successfully delivered, all future search messages from u to v succeed as well. We call this property monotonic searchability. We show that in general it is impossible to provide monotonic searchability if corrupted messages are present in the system, which justifies the restriction to system states without corrupted messages. Furthermore, we provide a self-stabilizing protocol for the line for which we can also show monotonic searchability. It turns out that even for the line it is non-trivial to achieve this property. Additionally, we extend our protocol to deal with node departures in terms of the Finite Departure Problem of Foreback et. al (SSS 2014). This makes our protocol even capable of handling node dynamics.

Towards a Universal Approach for the Finite Departure Problem in Overlay Networks - Koutsopoulos, Andreas; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 17th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
A fundamental problem for overlay networks is to safely exclude leaving nodes, i.e., the nodes requesting to leave the overlay network are excluded from it without affecting its connectivity. There are a number of studies for safe node exclusion if the overlay is in a well-defined state, but almost no formal results are known for the case in which the overlay network is in an arbitrary initial state, i.e., when looking for a self-stabilizing solution for excluding leaving nodes. We study this problem in two variants: the Finite Departure Problem (FDP) and the Finite Sleep Problem (FSP). In the FDP the leaving nodes have to irrevocably decide when it is safe to leave the network, whereas in the FSP, this leaving decision does not have to be final: the nodes may resume computation when woken up by an incoming message. We are the first to present a self-stabilizing protocol for the FDP and the FSP that can be combined with a large class of overlay maintenance protocols so that these are then guaranteed to safely exclude leaving nodes from the system from any initial state while operating as specified for the staying nodes. In order to formally define the properties these overlay maintenance protocols have to satisfy, we identify four basic primitives for manipulating edges in an overlay network that might be of independent interest.

The impact of communication patterns on distributed locally self-adjusting binary search trees - Strothmann, Thim Frederik (Proceedings of the 9th International Workshop on Algorithms and Computation (WALCOM))
This paper introduces the problem of communication pattern adaption for a distributed self-adjusting binary search tree. We propose a simple local algorithm, which is closely related to the nearly thirty-year-old idea of splay trees and evaluate its adaption performance in the distributed scenario if different communication patterns are provided.To do so, the process of self-adjustment is modeled similarly to a basic network creation game, in which the nodes want to communicate with only a certain subset of all nodes. We show that, in general, the game (i.e., the process of local adjustments) does not converge, and convergence is related to certain structures of the communication interests, which we call conflicts.We classify conflicts and show that for two communication scenarios in which convergence is guaranteed, the self-adjusting tree performs well.Furthermore, we investigate the different classes of conflicts separately and show that, for a certain class of conflicts, the performance of the tree network is asymptotically as good as the performance for converging instances. However, for the other conflict classes, a distributed self-adjusting binary search tree adapts poorly.

The complexity of pure equilibria in mix-weighted congestion games on parallel links - Monien, Burkhard; Mavronicolas, Marios (Information Processing Letters)
We revisit the simple class of weighted congestion games on parallel links [10], where each player has a non-negative weight and her cost on the link she chooses is the sum of the weights of all players choosing the link. We extend this class to mix-weighted congestion games on parallel links, where weights may as well be negative. For the resulting simple class, we study the complexity of deciding the existence of a pure equilibrium, where no player could unilaterally improve her cost by switching to another link.We show that even for a singlenegative weight, this decision problem is strongly NP-complete when the number of links is part of the input; the problem is NP-complete already for two links. When the number of links is a fixed constant, we show, through a pseudopolynomial, dynamic programming algorithm, that the problem is not strongly NP-complete unless P = NP; the algorithm works for any number of negative weights.

Systematically Deriving Quality Metrics for Cloud Computing Systems - Becker, Matthias; Lehrig, Sebastian; Becker, Steffen (Proceedings of the 6th ACM/SPEC International Conference on Performance Engineering)
In cloud computing, software architects develop systems for virtually unlimited resources that cloud providers account on a pay-per-use basis. Elasticity management systems provision these resources autonomously to deal with changing workload. Such changing workloads call for new objective metrics allowing architects to quantify quality properties like scalability, elasticity, and efficiency, e.g., for requirements/SLO engineering and software design analysis. In literature, initial metrics for these properties have been proposed. However, current metrics lack a systematic derivation and assume knowledge of implementation details like resource handling. Therefore, these metrics are inapplicable where such knowledge is unavailable.To cope with these lacks, this short paper derives metrics for scalability, elasticity, and efficiency properties of cloud computing systems using the goal question metric (GQM) method. Our derivation uses a running example that outlines characteristics of cloud computing systems. Eventually, this example allows us to set up a systematic GQM plan and to derive an initial set of six new metrics. We particularly show that our GQM plan allows to classify existing metrics.

Bonding of Wood Plastic Composites (WPC) - Material and Surface Modification for Special Applications - Moritzer, Elmar; Hopp, Matthias (68th Annual Assembly of the International Institute of Welding (IIW))

Kleben von Wood-Plastic-Composites (WPC) - Material- und Oberflächenmodifizierung für spezielle Anwendungen - Moritzer, Elmar; Hopp, Matthias (Jahresmagazin Kunststofftechnik)

Systematic Development and Re-Use of Model Tranformations - Besova, Galina

SynRace: Decentralized Load-Adaptive Multi-path Routing without Collecting Statistics - Schwabe, Arne; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
Multi-rooted trees are becoming the norm for modern data-center networks. In these networks, scalable flow routing is challenging owing to vast number of flows. Current approaches either employ a central controller that can have scalability issues or a scalable decentralized algorithm only considering local information. In this paper we present a new decentralized approach to least-congested path routing in software-defined data center networks that has neither of these issues: By duplicating the initial (or SYN) packet of a flow and estimating the data rate of multiple flows in parallel, we exploit TCP’s habit to fill buffers to find the least congested path. We show that our algorithm significantly improves flow completion time without the need for a central controller or specialized hardware.

Reputation und Vertrauen auf Online-Märkten - Sonntag, Melissa

Rating Aggregation in Multi-Dimensional Rating Systems: How Do Reviewers Form Overall Ratings? - Gutt, Dominik; Kundisch, Dennis (INFORMS Annual Meeting)

Quantitative Evaluation of Model-Driven Performance Analysis and Simulation of Component-based Architectures - Brosig, Fabian; Meier, Philipp; Becker, Steffen; Koziolek, Anne; Koziolek, Heiko; Kounev, Samuel (Transactions on Software Engineering)
During the last decade, researchers have proposed a number of model transformations enabling performance predictions. These transformations map performance-annotated software architecture models into stochastic models solved by analytical means or by simulation. However, so far, a detailed quantitative evaluation of the accuracy and efﬁciency of different transformations is missing, making it hard to select an adequate transformation for a given context. This paper provides an in-depth comparison and quantitative evaluation of representative model transformations to, e.g., Queueing Petri Nets and Layered Queueing Networks. The semantic gaps between typical source model abstractions and the different analysis techniques are revealed. The accuracy and efﬁciency of each transformation are evaluated by considering four case studies representing systems of different size and complexity. The presented results and insights gained from the evaluation help software architects and performance engineers to select the appropriate transformation for a given context, thus signiﬁcantly improving the usability of model transformations for performance prediction.

Protokolle zur authentifizierten Schüsselvereinbarung - Eisenhofer, Thorsten

Evaluation of the Efficiency of Filtration Processes Using Precoat Materials - Schiller, Sascha; Hellmich, Christoph; Schmid, Hans-Joachim (Chemical Engineering & Technology)
The highly efficient filtration of ultrafine dust emitted by biomass combustion processes with a baghouse filter has been successfully tested in the last years. To protect the filter material from the very small and sticky fine dust particles and to guarantee very high total collection efficiencies (> 99 %) in a long-term stable process, the use of a precoat is necessary. Tests done in a laboratory and a real-application plant show that the reuse of precoat materials can lead to significant savings. Considering the influences of different combustion processes, the associated precoat efficiencies could be calculated. With these characteristic ratios, it is possible to evaluate different process settings. Hence, the amount and the cost of the needed precoat could be reduced significantly.

Process Development of a Liquid-Liquid Phase Transfer of Colloidal Particles for Production of High-Quality Organosols - Erler, Jacqueline V.; Machunsky, Stefanie; Franke, Steffen; Grimm, Philipp; Schmid, Hans-Joachim; Peuker, Urs A. (Colloid Process Engineering)
The emphasis of the study presented is on a new process of particle extraction to transfer magnetite nanoparticles from an aqueous into an immiscible organic phase directly through the liquid-liquid interface. For the production of high-quality organosols, stabilized colloidal and functionalized particles are required in a liquid organic phase. The mechanism of phase transfer is initiated by adsorption and chemical binding of surfactants (fatty acids) at the particle surface. The resulting physico-chemical dispersion of the hydrophobically modified particles leads to the formation of the stabilized organic colloid, or organosol. The aim here is to demonstrate the entire chain of the transfer process in a continuous miniplant, which comprises particle synthesis, conditioning, and transfer, and which uses a drop column for extraction and as a transfer device. Based on the investigation of the governing principles and the material parameters, the results obtained for the transfer kinetics in the individual contact devices (centrifuge, single-drop column, and drop column for different operations) are used for the dimensioning of the entire process chain.

Bipolar charge distribution of a soft X-ray diffusion charger - Tigges, L.; Wiedensohler, A.; Weinhold, K.; Gandhi, J.; Schmid, Hans-Joachim (Journal of Aerosol Science)
The conditioning of the aerosol particle population into a bipolar charge equilibrium is an essential prerequisite to calculate the particle number size distribution using mobility particle size spectrometers. This is commonly realized by diffusion charging of bipolar air ions generated by e.g. a 85Kr source. Because of strict legal regulations on radioactive sources in several countries, soft-X-ray (SXR) appears as a suitable alternative. However, multiple measurements showed a systematical and significant difference between the particle charge distribution delivered by a radioactive source and an SXR charger, respectively. In this investigation, a calibrated particle charge distribution, suitable for the SXR chargers, was calculated based on the Fuchs model. An approximation analogous to the commonly used Wiedensohler approximation formula (Wiedensohler, 1988) was computed. The use of the new SXR approximation of the bipolar charge equilibrium for the inversion of an electrical mobility distribution to a particle number size distribution improves the comparability of these results, compared to measurements involving a 85Kr charger or to bipolar chargers using radioactive material in general. A systematic error in case of using the SXR charger could be eliminated and hence the root mean square deviation could be reduced from 13% using the common parameters for both charger types to 7% using the new SXR approximation for the SXR bipolar charger.

On the bipolar charge distribution used for mobility particle sizing: Theoretical considerations - Tigges, L.; Jain, A.; Schmid, Hans-Joachim (Journal of Aerosol Science)
An essential part of mobility particle size spectroscopy is the prediction of the aerosol charge distribution in a highly concentrated bipolar ion environment. This charge distribution can be readily calculated, but is depending on several environmental conditions. These influences are investigated theoretically. The first part of this work deals with a sensitivity analysis using the Fuchs model (Fuchs, 1963) to determine the variation of the resulting charge distributions depending on the input parameters. It is demonstrated, that the main influencing variable is the difference between the positive and negative ion mobility. A sensitivity analysis reveals that a reasonable variation of the ion mobilities may lead to variations of the particle density distribution up to±20%. The second part investigates the evolution of the charge distribution along the tubing downstream of the bipolar charger exit starting with equal ion concentrations for positive and negative ions. Due to wall losses depending on ion mobility a non-equilibrium charge distribution is developing along the plumbing. The evolution of the particle charge distribution is determined using a coupled population balance model. Even though the non-equilibrium character is clearly shown, it turns out that this effect is negligible at conditions typical for particle size measurements.

Highly efficient filtration of ultrafine dust in baghouse filters using precoat materials - Schiller, Sascha; Schmid, Hans-Joachim (Powder Technology)
The precipitation of sticky and ultrafine particles has become increasingly important. Biomass burners are one important example for ultrafine dust emission sources with ever growing importance. Therefore, a baghouse filter has been developed, which combines excellent separation efficiency (> 99%, clean air dust loading of < 1 mg/m3) with convenience in operation. However, in order to prevent clogging of the filter cloth by sticky and ultrafine particles, it is necessary to use a precoat layer (e.g. hydrated limestone powder). If this technology is applied to larger scale processes, e.g. biomass burning for industrial drying processes, the reuse of the precoat material can generate significant savings. Therefore, extended tests on recycling of used precoat material have been performed. Particularly, the influence of precoat injection parameters and various mixing strategies of used and virgin powder for refreshing the precoat material have been investigated. Different mixtures have been characterised by their ability to disintegrate, flowability and filtration behaviour. It is clearly demonstrated that upon redispersing the used precoat fine dust mainly adheres to the coarse precoat with only a limited number of dust agglomerates being produced in addition. For each kind of precoat a minimum amount is determined in order to ensure a long-term stable process. This way a saving potential of between 40–67% has been found. An economic and ecologic process has been developed to precipitate ultrafine dust in a baghouse filter system using precoat materials.

Simulation of Capillary Bridges between Particles - Dörmann, Michael; Schmid, Hans-Joachim (Procedia Engineering)
Capillary forces between particles often dominate other adhesion forces. However, the calculation of the shape of capillary bridges and the resulting force is complex, so often assumptions and approximations are used. These assumptions are not useful for nanoscale particles. Therefore, a simulation method was established to calculate numerically the shape of the meniscus and derive the corresponding capillary bridge force. The main focus are nanoscaled particles with liquid bridges formed by condensing air humidity. The dependence of the capillary force on various parameters such as particle sizes, contact angle and humidity was investigated and it is demonstrated that often-used assumptions cannot be used for nanoscaled particles without remarkable mistake.

Unscharfe Produktionsmengenplanung als Instrument des Risikomanagements in Supply Chains - Betz, Stefan (Risikomanagement in Supply Chains)

Bedarfsorientiertes Kapazitätsmanagement in Supply Chains - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Dual-path source engineering in integrated quantum optics - Kruse, Regina; Sansoni, Linda; Brauner, Sebastian; Ricken, Raimund; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review A)

Programs from Proofs of Predicated Dataflow Analyses - Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the 30th Annual ACM Symposium on Applied Computing)
Programs from Proofs" is a generic method which generates new programs out of correctness proofs of given programs. The technique ensures that the new and given program are behaviorally equivalent and that the new program is easily verifiable, thus serving as an alternative to proof-carrying code concepts. So far, this generic method has one instantiation that verifies type-state properties of programs. In this paper, we present a whole range of new instantiations, all based on data ow analyses. More precisely, we show how an imprecise but fast data ow analysis can be enhanced with a predicate analysis as to yield a precise but expensive analysis. Out of the safety proofs of this analysis, we generate new programs, again behaviorally equivalent to the given ones, which are easily verifiable" in the sense that now the data ow analysis alone can yield precise results. An experimental evaluation practically supports our claim of easy verification.

20 Jahre Lernen mit dem World Wide Web - Technik und Bildung im Dialog - Keil, Reinhard; Harald, Selke

Systematik zur Entwicklung einer produktlebenszyklusorientierten Geschäftsmodell-Roadmap - Peitz, Christoph

Systematik zur frühzeitigen Absicherung der Sicherheit und Zuverlässigkeit fortschrittlicher mechatronischer Systeme - Dorociak, Rafal

Augmented & Virtual Reality in der Produktentstehung: Grundlagen, Methoden und Werkzeuge; Interaktions- und Visualisierungstechniken, Virtual Prototyping intelligenter technischer Systeme mit AR/VR - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Systematik zur wirtschaftlichkeitsorientierten Konzipierung Intelligenter Technischer Systeme - Vaßholz, Mareen

Verification and Simulation of Self-Adaptive Mechatronic Systems - Heinzemann, Christian

Optimizing Water Tanks in Water Distribution Systems by combining Network Reduction, Mathematical Optimization and Hydraulic Simulation - Hallmann, Corinna; Suhl, Leena (OR Spectrum)
In the last two decades, water consumption in Germany has been decreasing, which causes the water tanks and pipes in water distribution systems to work inefficiently. This paper proposes a method that supports the planning process for tanks in water distribution systems. The method uses a combination of network reduction, mathematical optimization and hydraulic simulation. The mathematical optimization model is a non-convex Mixed Integer Quadratically Constrained Program (MIQCP) that is solved by a piecewise linearization. As this may lead to many binary variables and therefore high computing times, the size of the water distribution system model is reduced before building the optimization model. After applying several network reduction techniques and using a piecewise approximation of the original model, there may be some hydraulic differences between the original network model and the reduced network model. To make sure that the solution obtained in the optimization process is feasible in the original water distribution system model, the solution is verified by a hydraulic simulation. If the solution is not feasible, the reduced model has to be modified and solved again until the hydraulic simulation verifies a solution as feasible. In this paper, each of these processes is described and the results indicate the usefulness of each of them.

Homodyne detection with on-off detector systems - Lipfert, T.; Sperling, Jan; Vogel, W. (Physical Review A)

Continuous sampling of the squeezed-state nonclassicality - Agudelo, E.; Sperling, Jan; Vogel, W.; Köhnke, S.; Mraz, M.; Hage, B. (Physical Review A)

Unified nonclassicality criteria - Ryl, S.; Sperling, Jan; Agudelo, E.; Mraz, M.; Köhnke, S.; Hage, B.; Vogel, W. (Physical Review A)

Convex ordering and quantification of quantumness - Sperling, Jan; Vogel, W (Physica Scripta)

Entanglement and phase properties of noisy NOON states - Bohmann, M.; Sperling, Jan; Vogel, W. (Physical Review A)

Entanglement witnesses for indistinguishable particles - Reusch, A.; Sperling, Jan; Vogel, W. (Physical Review A)

Nonclassicality Phase-Space Functions: More Insight with Fewer Detectors - Luis, Alfredo; Sperling, Jan; Vogel, Werner (Physical Review Letters)

Balanced homodyne detection with on-off detector systems: Observable nonclassicality criteria - Sperling, Jan; Vogel, W.; Agarwal, G. S. (EPL (Europhysics Letters))

Full Multipartite Entanglement of Frequency-Comb Gaussian States - Gerke, S.; Sperling, Jan; Vogel, W.; Cai, Y.; Roslund, J.; Treps, N.; Fabre, C. (Physical Review Letters)

Optimizing Software-Defined Networks using Application-Layer Knowledge - Wette, Philip

An overview of the BIOASQ large-scale biomedical semantic indexing and question answering competition - Tsatsaronis, George; Balikas, Georgios; Malakasiotis, Prodromos; Partalas, Ioannis; Zschunke, Matthias; R. Alvers, Michael; Weissenborn, Dirk; Krithara, Anastasia; Petridis, Sergios; Polychronopoulos, Dimitris; Almirantis, Yannis; Pavlopoulos, John; et al. (BMC Bioinform.)

Linked SDMX Data: Path to high fidelity Statistical Linked Data - Capadisli, Sarven; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

Semantic Quran - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Semantic Web)

SINA: Semantic interpretation of user queries for question answering on interlinked data - Shekarpour, Saeedeh; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille; Auer, Sören (J. Web Semant.)

DeFacto - Temporal and multilingual Deep Fact Validation - Gerber, Daniel; Esteves, Diego; Lehmann, Jens; Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Speck, René (J. Web Semant.)

Question Answering over Linked Data (QALD-5) - Unger, Christina; Forascu, Corina; López, Vanessa; Ngonga Ngomo, Axel-Cyrille; Cabrio, Elena; Cimiano, Philipp; Walter, Sebastian (Working Notes of CLEF 2015 - Conference and Labs of the Evaluation forum, Toulouse, France, September 8-11, 2015)

HAWK@QALD5 - Trying to Answer Hybrid Questions with Various Simple Ranking Techniques - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Working Notes of CLEF 2015 - Conference and Labs of the Evaluation forum, Toulouse, France, September 8-11, 2015)

CETUS - A Baseline Approach to Type Extraction - Röder, Michael; Usbeck, Ricardo; Speck, René; Ngonga Ngomo, Axel-Cyrille (Semantic Web Evaluation Challenges - Second SemWebEval Challenge at ESWC 2015, Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

Developing a Sustainable Platform for Entity Annotation Benchmarks - Röder, Michael; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ESWC Developers Workshop 2015 co-located with the 12th Extended Semantic Web Conference {(ESWC} 2015), Portorož, Slovenia, May 31, 2015)

Evaluating Entity Annotators Using GERBIL - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2015 Satellite Events - ESWC 2015 Satellite Events Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

Developing a Sustainable Platform for Entity Annotation Benchmarks - Röder, Michael; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2015 Satellite Events - ESWC 2015 Satellite Events Portorož, Slovenia, May 31 - June 4, 2015, Revised Selected Papers)

HAWK - Hybrid Question Answering Using Linked Data - Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille; Bühmann, Lorenz; Unger, Christina (The Semantic Web. Latest Advances and New Domains - 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31 - June 4, 2015. Proceedings)

Automating RDF Dataset Transformation and Enrichment - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (The Semantic Web. Latest Advances and New Domains - 12th European Semantic Web Conference, ESWC 2015, Portoroz, Slovenia, May 31 - June 4, 2015. Proceedings)

LODFlow: a workflow management system for linked data processing - Rautenberg, Sandro; Ermilov, Ivan; Marx, Edgard; Auer, Sören; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Conference on Semantic Systems, SEMANTICS 2015, Vienna, Austria, September 15-17, 2015)

An optimization approach for load balancing in parallel link discovery - Ahmed Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 11th International Conference on Semantic Systems, SEMANTICS 2015, Vienna, Austria, September 15-17, 2015)

Motive-based Search - Avdiyenko, Liliya; Nettling, Martin; Lemke, Christiane; Wauer, Matthias; Ngonga Ngomo, Axel-Cyrille; Both, Andreas (KDIR 2015 - Proceedings of the International Conference on Knowledge Discovery and Information Retrieval, part of the 7th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management {(IC3K} 2015), Volume 1, Lisbon, Portugal, November 12-14, 2015)

Using Caching for Local Link Discovery on Large Data Sets - M. Hassan, Mofeed; Speck, René; Ngonga Ngomo, Axel-Cyrille (Engineering the Web in the Big Data Era - 15th International Conference, ICWE 2015, Rotterdam, The Netherlands, June 23-26, 2015, Proceedings)

DeLFI 2015 - The 13th e-Learning Conference on Computer Science of the E-Learning Section of the Society for Computer Science eV - Pongratz, Hans; Keil, Reinhard

FEASIBLE: A Feature-Based SPARQL Benchmark Generation Framework - Saleem, Muhammad; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part I)

ASSESS - Automatic Self-Assessment Using Linked Data - Bühmann, Lorenz; Usbeck, Ricardo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part II)

WebArena - R {\ "a} spacious structures for ü r the learning locations of the future - Winkelnkemper, Felix; Oberhoff, Andreas

An Open Question Answering Framework - Marx, Edgard; Soru, Tommaso; Esteves, Diego; Ngonga Ngomo, Axel-Cyrille; Lehmann, Jens (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

LSQ: The Linked SPARQL Queries Dataset - Saleem, Muhammad; Intizar Ali, Muhammad; Hogan, Aidan; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part II)

The LSQ Dataset: Querying for Queries - Saleem, Muhammad; Intizar Ali, Muhammad; Hogan, Aidan; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Automatic SPARQL Benchmark Generation using FEASIBLE - Saleem, Muhammad; Mehmood, Qaiser; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

LANCE: Piercing to the Heart of Instance Matching Tools - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2015 - 14th International Semantic Web Conference, Bethlehem, PA, USA, October 11-15, 2015, Proceedings, Part I)

LANCE: A Generic Benchmark Generator for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Enhancing Dataset Quality using Keys - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the ISWC 2015 Posters {&} Demonstrations Track co-located with the 14th International Semantic Web Conference (ISWC-2015), Bethlehem, PA, USA, October 11, 2015)

Interlinking: Performance Assessment of User Evaluation vs. Supervised Learning Approaches - M. Hassan, Mofeed; Lehmann, Jens; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Workshop on Linked Data on the Web, LDOW 2015, co-located with the 24th International World Wide Web Conference {(WWW} 2015), Florence, Italy, May 19th, 2015)

Pushing the Limits of Instance Matching Systems: A Semantics-Aware Benchmark for Linked Data - Saveta, Tzanina; Daskalaki, Evangelia; Flouris, Giorgos; Fundulaki, Irini; Herschel, Melanie; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

CubeViz: Exploration and Visualization of Statistical Linked Data - Martin, Michael; Abicht, Konrad; Stadler, Claus; Ngonga Ngomo, Axel-Cyrille; Soru, Tommaso; Auer, Sören (Proceedings of the 24th International Conference on World Wide Web Companion, WWW 2015, Florence, Italy, May 18-22, 2015 - Companion Volume)

ROCKER: A Refinement Operator for Key Discovery - Soru, Tommaso; Marx, Edgard; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

GERBIL: General Entity Annotator Benchmarking Framework - Usbeck, Ricardo; Röder, Michael; Ngonga Ngomo, Axel-Cyrille; Baron, Ciro; Both, Andreas; Brümmer, Martin; Ceccarelli, Diego; Cornolti, Marco; Cherix, Didier; Eickmann, Bernd; Ferragina, Paolo; Lemke, Christiane; et al. (Proceedings of the 24th International Conference on World Wide Web, WWW 2015, Florence, Italy, May 18-22, 2015)

Managing Geospatial Linked Data in the GeoKnow Project - Lehmann, Jens; Athanasiou, Spiros; Both, Andreas; García-Rojas, Alejandra; Giannopoulos, Giorgos; Hladky, Daniel; Jay Le Grange, Jon; Ngonga Ngomo, Axel-Cyrille; Ahmed Sherif, Mohamed; Stadler, Claus; Wauer, Matthias; Westphal, Patrick; et al. (The Semantic Web in Earth and Space Science. Current Status and Future Directions)

Microwave Experiments Simulating Quantum Search and Directed Transport in Artificial Graphene - Böhm, Julian; Bellec, Matthieu; Mortessagne, Fabrice; Kuhl, Ulrich; Barkhofen, Sonja; Gehler, Stefan; Stöckmann, Hans-Jürgen; Foulger, Iain; Gnutzmann, Sven; Tanner, Gregor (Physical Review Letters)

Compounding approach for univariate time series with nonstationary variances - Schäfer, Rudi; Barkhofen, Sonja; Guhr, Thomas; Stöckmann, Hans-Jürgen; Kuhl, Ulrich (Physical Review E)

Optimierung von Wasserbehältern in einem Wasserversorgungssystem mittels einer Kombination aus Netzreduktion, mathematischer Optimierung und hydraulischer Simulation - Hallmann, Corinna

Quantum walk coherences on a dynamical percolation graph - Elster, Fabian; Barkhofen, Sonja; Nitsche, Thomas; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Silberhorn, Christine (Scientific Reports)

20 years of learning with the World Wide Web - technology and education in dialogue

Learn with, through and {\ "about the WWW - Keil, Reinhard; Selke, Harald

Virtual knowledge {\ "a} ume - From the presentation of content to virtual learning ä tten - Keil, Reinhard; Selke, Harald

Development of a structured process of interaction design for {\ "u} r nat ü local user interfaces - Klompmaker, Florian

Empirical validation of design patterns - Schild, Christian; Petrausch, Vanessa (Human and Computer 2015 - Proceedings)
Patterns serve to codify design knowledge. By embedding them in a hypothesis-driven design, it is possible to develop them further into sample languages. For this it is necessary to resolve the underlying conflicts in the form of design hypotheses and to validate them empirically in order to enable further use and generalization. In this article, an experiment is presented that describes this procedure and demonstrates the interplay between theory formation and codification of design knowledge using two examples.

Online Resource Leasing - Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 2015 ACM Symposium on Principles of Distributed Computing (PODC))
Many markets have seen a shift from the idea of buying and moved to leasing instead. Arguably, the latter has been the major catalyst for their success. Ten years ago, research realized this shift and initiated the study of "online leasing problems" by introducing leasing to online optimization problems. Resources required to provide a service in an "online leasing problem" are no more bought but leased for different durations. In this paper, we provide an overview of results that contribute to the understanding of "online resource leasing problems".

Einstellungen von Grundschullehrkräften zum inklusiven Lernen in Abhängigkeit von dem Umfang an Erfahrungen aus dem Unterricht mit Kindern mit unterschiedlichen sonderpädagogischen Förderbedarfen - Hellmich, Frank; Görel, Gamze (Veränderung und Beständigkeit in Zeiten der Inklusion. Perspektiven sonderpädagogischer Professionalisierung)

Online Resource Leasing - Markarian, Christine

Entwicklung naturwissenschaftlich-technischer Lehr-Lernangebote für inklusiven Sachunterricht - Blumberg, Eva; Hellmich, Frank; Fromme, Theresa (Lernprozessbegleitung und adaptives Lernen in der Grundschule. Forschungsbezogene Beiträge)

Kausalattributionen von Leseerfolgen und Lesemisserfolgen bei Kindern im Leseunterricht der Grundschule - Ort, Margarita; Hellmich, Frank (Facetten grundschulpädagogischer und -didaktischer Forschung)

Lesestrategien und Leseerfolg bei Kindern im vierten Grundschuljahr – Analysen mit Fragebogen- und Beobachtungsverfahren - Hellmich, Frank (Innovative Erhebungsmethoden – dargestellt an verschiedenen Forschungsprojekten)